2007
DOI: 10.1074/jbc.m704616200
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Function Characterization of μ-Conotoxin KIIIA, an Analgesic, Nearly Irreversible Blocker of Mammalian Neuronal Sodium Channels

Abstract: Peptide neurotoxins from cone snails continue to supply compounds with therapeutic potential. Although several analgesic conotoxins have already reached human clinical trials, a continuing need exists for the discovery and development of novel nonopioid analgesics, such as subtype-selective sodium channel blockers. -Conotoxin KIIIA is representative of -conopeptides previously characterized as inhibitors of tetrodotoxin (TTX)-resistant sodium channels in amphibian dorsal root ganglion neurons. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
263
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 136 publications
(307 citation statements)
references
References 44 publications
36
263
3
2
Order By: Relevance
“…Conversely, KIIIA is a shorter peptide of only 16 aa that also blocks Na + ion conductance through Nav1.4. However, the blockage by KIIIA is incomplete, allowing guanidinium toxins like tetrodotoxin (TTX) access to a deeper pocket of site 1 of most Nav isoforms, as indicated by experiments where complete block is achieved when TTX and KIIIA are applied simultaneously (21,22,30,32).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, KIIIA is a shorter peptide of only 16 aa that also blocks Na + ion conductance through Nav1.4. However, the blockage by KIIIA is incomplete, allowing guanidinium toxins like tetrodotoxin (TTX) access to a deeper pocket of site 1 of most Nav isoforms, as indicated by experiments where complete block is achieved when TTX and KIIIA are applied simultaneously (21,22,30,32).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, SIIIA and KIIIA have a much shorter loop 2 and a lysine instead of an arginine in the corresponding position. Recent structure-activity studies on TIIIA (15) and KIIIA (20) have confirmed that the arginine in loop 2 is crucial for TIIIA affinity at both neuronal and skeletal muscle sodium channels, whereas the structurally equivalent lysine was only important for affinity at the skeletal muscle VGSC. Three-dimensional structures of -conotoxins GIIIA, GIIIB, PIIIA, TIIIA, and SmIIIA have been determined by NMR (14,15,17,26,27).…”
mentioning
confidence: 99%
“…-Conotoxins GIIIA, GIIIB, and GIIIC from Conus geographus selectively target the skeletal muscle Na v 1.4, PIIIA from Conus purpurasence (12)(13)(14) and TIIIA from Conus tulipa (15) target Na v 1.2 and 1.4, and -conotoxins SmIIIA from Conus stercusmuscsarum (16,17), SIIIA from Conus striatus (18,19), and KIIIA from Conus kinoshitai (18) target amphibian TTX-R sodium channels. More recently, KIIIA has also been shown to inhibit TTX-S sodium channels in mouse DRG and rat TTX-S sodium channels expressed in Xenopus oocytes (20). Lastly, -conotoxins CnIIIA, CnIIIB from Conus consors, CIIIA from Conus catus, and MIIIA from Conus magus were found to inhibit TTX-R and TTX-S sodium channels in frog DRG but not rat or mouse DRG neurons (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ещё более универсальное действие на ТТХ-чувствительные натриевые каналы характерно для недавно описанного m-конотоксина KIIIA [62]. Тестирование на периферических нейронах мыши показало, что этот токсин необратимо ингибирует 80% ТТХ-чувствительных каналов и лишь 20% ТТХ-устойчивых.…”
Section: структура потенциалзависимых ионных каналов и разнообразие иunclassified